Prevalence of Thyroid Disorder in Pregnant Women Visiting a Tertiary Care Teaching Hospital: A Descriptive Cross-sectional Study - Gita Khakurel; Chandrima Karki; Sanat Chalise (Journal of Nepal Medical Association, 2020)
Introduction: The function of the thyroid gland is altered during pregnancy. Thyroid disorders during pregnancy are associated with serious maternal and fetal outcomes. Universal screening for thyroid disorders is recommended in the first trimester of pregnancy. This study aims to determine the prevalence of thyroid disorder during pregnancy in women attending a tertiary care hospital.